2013
DOI: 10.1038/jid.2012.489
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Regulates Cell Migration during Skin Wound Healing

Abstract: Precise orchestration of actin polymer into filaments with distinct characteristics of stability, bundling, and branching underpins cell migration. A key regulator of actin filament specialization is the tropomyosin family of actin-associating proteins. This multi-isoform family of proteins assemble into polymers that lie in the major groove of polymerized actin filaments, which in turn determine the association of molecules that control actin filament organization. This suggests that tropomyosins may be impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
(70 reference statements)
3
36
0
Order By: Relevance
“…Changed expression levels of the different tropomyosin isoforms may therefore coordinate actin and adhesion dynamics to generate discrete migration outcomes. The synchronizing effects of Tm5NM1 on focal adhesion and actin filament stability are in line with the in vivo role we have described for Tm5NM1 during skin wound healing (34). Wound healing is a precisely orchestrated series of timed migration events that are necessary for efficient wound closure.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Changed expression levels of the different tropomyosin isoforms may therefore coordinate actin and adhesion dynamics to generate discrete migration outcomes. The synchronizing effects of Tm5NM1 on focal adhesion and actin filament stability are in line with the in vivo role we have described for Tm5NM1 during skin wound healing (34). Wound healing is a precisely orchestrated series of timed migration events that are necessary for efficient wound closure.…”
Section: Discussionsupporting
confidence: 49%
“…As we have reported previously, the loss of Tm5NM1 expression induced increased formation of focal complexes, contrasting with the loss of focal complexes in cells with high-level Tm5NM1 expression (Fig. 2C) (4,34). Assessment of Src kinase activity by an in vitro kinase activity assay reveals ϳ2-fold-higher activity in Tm5NM1…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Tropomyosin is a multi-isoform family of actin-associating proteins that controls isoform-specific regulation of diverse actin filaments (Bach et al, 2009;Gunning et al, 2005). A recent report by Lees et al (2013) suggested that the tropomyosin may be important regulators of actin functioning during the wound healing process. In short, actin, myosin and tropomysosin are directly involved in the regulation and maintenance of wound recovery.…”
Section: Actin Myosin and Tropomyosinmentioning
confidence: 99%
“…There is a possibility that some of the proteins identified in BD and SD could be associated with speeding up wound healing. It is interesting to note that some cytoskeletal proteins including actin [148][149][150][151][152], profilin [153,154], alpha tubulin [154], calponin [155,156], nonmuscle myosin [149,157,158], thymosin [159], and tropomyosin [160] identified at high abundance in BD and SD saliva were associated with different aspects of wound healing. Could secretion of these proteins at high abundance be the tick's way to help the host heal?…”
Section: Housekeeping Proteins and Other Tspsmentioning
confidence: 99%